2013
DOI: 10.1002/path.4158
|View full text |Cite
|
Sign up to set email alerts
|

Combining integrated genomics and functional genomics to dissect the biology of a cancer‐associated, aberrant transcription factor, the ASPSCR1–TFE3 fusion oncoprotein

Abstract: Oncogenic rearrangements of the TFE3 transcription factor gene are found in two distinct human cancers. These include ASPSCR1–TFE3 in all cases of alveolar soft part sarcoma (ASPS) and ASPSCR1–TFE3, PRCC-TFE3, SFPQ-TFE3 and others in a subset of paediatric and adult RCCs. Here we examined the functional properties of the ASPSCR1–TFE3 fusion oncoprotein, defined its target promoters on a genome-wide basis and performed a high-throughput RNA interference screen to identify which of its transcriptional targets co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 48 publications
2
61
0
5
Order By: Relevance
“…Exogenous lactate drove increases in proliferative index and vascular density (Fig.8D–F). As cross-validation of this effect, we cultured the only two described human cancer cell lines that express ASPSCR1-TFE3 , FU-UR-1 (Ishiguro et al, 2004; Kobos et al, 2013) and ASPS-1 (Kenney et al, 2011) in increasing concentrations of sodium lactate, identifying a proliferative response. We further confirmed that increased exogenous lactate concentration in normoxia drove higher HIF1α stabilization, evidenced by its increased nuclear presence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous lactate drove increases in proliferative index and vascular density (Fig.8D–F). As cross-validation of this effect, we cultured the only two described human cancer cell lines that express ASPSCR1-TFE3 , FU-UR-1 (Ishiguro et al, 2004; Kobos et al, 2013) and ASPS-1 (Kenney et al, 2011) in increasing concentrations of sodium lactate, identifying a proliferative response. We further confirmed that increased exogenous lactate concentration in normoxia drove higher HIF1α stabilization, evidenced by its increased nuclear presence.…”
Section: Resultsmentioning
confidence: 99%
“…Although many angiogenic genes are highly upregulated in the tumors (Lazar et al, 2007; Vistica et al, 2009), few were found to be direct transcriptional targets of the fusion protein by chromatin immunoprecipitation analyses (Kobos et al, 2013). This suggests that some other factor, possibly related to metabolism or microenvironment, enhances angiogenesis in ASPS.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the one patient who has survived with no evidence of disease despite hematogenous metastasis (M1 disease; ASPSCR1-TFE3 Case 33) responded to immune therapy including tumor vaccine and interleukin 2 treatments, whereas these treatments have been ineffective in other patients (such as case 12 of reference 38 and case 2 of reference 26). These reports highlight that a single effective treatment remains out of reach at the current time for these neoplasms, and underscore the importance of further genetic analysis 66,67 to identify potential targets such as MET (known to be induced by TFE3 gene fusions 66 ) for effective, nontoxic therapies for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…A strong positive immunoreaction against TFE3 is characteristic for ASPS. 8,12,22 Treatment and outcomes Because of its rarity, unusual clinical course, and indolent disease progression, treatment for ASPS has been challenging for pathologists as well as surgeons. Radical surgical excision with 1.5-to 2.0-cm microscopically clear surgical margins of the primary tumoral tissue, as well as the recurrent tumor manifestation, seems to be essential for local control but is unable to prevent distant metastasis in case of early spreading.…”
Section: Discussion Clinical Featuresmentioning
confidence: 99%